Phenomenological Insight on Being Hindered From Fulfilling One’s Primary Responsibility to Educate Students - Collingridge, Dave S. (Alberta Journal of Educational Research, 2008)
The research literature suggests that a major challenge facing teachers today is being thwarted from fulfilling their primary responsibility to help students learn. Teachers who continually encounter circumstances that hinder their efforts to educate students are likely to experience workplace frustration and stress. Following the existential-phenomenological research approach, I conducted in-depth, private interviews with eight middle school teachers to reveal the psychological effect of workplace hindrances and to gain a deeper understanding of the experience underlying frustration. The salient experiential themes identified in this study are feeling disrespected, powerless, hopeless, upset/anger, and guilt. It is argued that we need to address these phenomenological constituents of being hindered and the contexts in which they occur if we hope seriously to mitigate the elevated levels of frustration and stress currently plaguing the profession.